Protocol for a study on the mental health and well-being of “Forgotten” first responders in Canada - Diana McGlinchey; Alyssa Ferns; Chris William Martin; Ashley Murfin; Kyle Killian; Jenna Row; Jalynn Countaway; McKenna Bellemare; Ocean Naneff; Amaya Purewal (PLoS ONE, 2026)
In addition to traditional first responders such as police, firefighters, and paramedics, there are many other workers who carry an occupational responsibility to respond to trauma. Such professions include but are not limited to correctional officers, frontline homeless shelter staff and security, harm reduction and supervised consumption site workers, and search and rescue teams. Research has demonstrated that individuals in these professions experience similar trauma-responses to first responders, albeit often without the same support and safeguards. The study described in this protocol paper aims to explore the burnout, compassion fatigue, and resilience experienced by these overlooked, “forgotten” first responders. Using a mixed methods approach, including an online survey, focus groups, and semi-structured interviews, the study will investigate burnout rates, compassion fatigue, coping strategies, vicarious resilience, and resources and barriers to well-being for the people doing this important work.